Determinación del efecto del helecho acuático azolla en la producción limpia de pimiento y tomate - Falcones Farfán, Hernán Steeven (2025)
Modern agriculture relies heavily on chemical fertilizers, which increase productivity but have negative impacts on the soil, the environment, and production costs. In this context, this study evaluated the effect of using Azolla caroliniana Lam. (Azolla) biomass and water as a biofertilizer on the yield of tomato (Solanum lycopersicum L.) and pepper (Capsicum annuum L.), compared to chemical fertilization (NPK) and a control without fertilization. A plot experimental design was used, recording production variables and performing an economic analysis to determine the viability of each treatment. In tomato, Azolla biomass achieved the highest production (40.84 kgplot), followed by NPK (33.66 kg), Azolla water (27.27 kg), and the control (21.36 kg), with a lower unit cost per kilogram (CPU) for Azolla biomass (2.33 USDkg). In pepper, Azolla biomass also recorded the highest production (1473.0 kgplot), followed by NPK (1396.5 kg), Azolla water (1231.05 kg), and the control (1064.7 kg), with a minimum CPU of 0.0266 USDkg. The results demonstrate that Azolla biomass not only improves the yield of both crops but also reduces the CPU compared to chemical fertilization. It is concluded that Azolla biomass constitutes a sustainable and economically viable alternative for horticultural production, reducing dependence on synthetic inputs and contributing to a more ecological, efficient, and lower-cost agriculture.